A Neutralizing Antibody Targeting Oxidized Phospholipids Promotes Bone Anabolism in Chow‐Fed Young Adult Mice. (29th September 2020) - Palmieri, Michela; Kim, Ha‐Neui; Gomez‐Acevedo, Horacio; Que, Xuchu; Tsimikas, Sotirios; Jilka, Robert L; Manolagas, Stavros C; Witztum, Joseph L; Ambrogini, Elena
ABSTRACT: Oxidized phospholipids containing phosphocholine (OxPL) are pro‐inflammatory lipid peroxidation products that bind to scavenger receptors (SRs), such as Scarb1, and toll‐like receptors (TLRs). Excessive OxPL, as found in oxidized low‐density lipoprotein (OxLDL), overwhelm these defense mechanisms and become pathogenic in atherosclerosis, nonalcoholic steatohepatitis (NASH), and osteoporosis. We previously reported that the innate IgM natural antibody E06 binds to OxPL and neutralizes their deleterious effects; expression of the single‐chain (scFv) form of the antigen‐binding domain of E06 (E06‐scFv) as a transgene increases trabecular bone in male mice. We show herein that E06‐scFv increases trabecular and cortical bone in female and male mice by increasing bone formation and decreasing osteoblast apoptosis in vivo. Homozygous E06‐scFv mice have higher bone mass than hemizygous, showing a dose effect of the transgene. To investigate how OxPL restrain bone formation under physiologic conditions, we measured the levels of SRs and TLRs that bind OxPL. We found that osteoblastic cells primarily express Scarb1. Moreover, OxLDL‐induced apoptosis and reduced differentiation were prevented in bone marrow–derived or calvaria‐derived osteoblasts from Scarb1 knockout mice. Because Scarb1‐deficient mice are reported to have high bone mass, our results suggest that E06 may promote bone anabolism in healthy young mice, at least in part, by neutralizing OxPL, which in turn promote Scarb1‐mediated apoptosis of osteoblasts or osteoblast precursors. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR)..